A cross-sectional study on the effect of dietary zinc intake on the relationship between serum vitamin D3 and HOMA-IR - Hu, Biao; Lin, Zheng-yang; Cai, Yuan; Sun, Yue-xin; Yang, Shu-qi; Guo, Jiang-long; Zhang, Shi; Sun, Dong-lin (Frontiers in Nutrition, 2022)
Introduction: Some studies have shown that serum vitamin D₃ concentration was associated with the risk of insulin resistance. At the same time, zinc is also important in the synthesis of vitamin D, because zinc is an important cofactor in activating vitamin D. However, not enough research has been done on whether dietary zinc intake affects the relationship between vitamin D₃ and the risk of insulin resistance. Accordingly, our study was designed as a cross-sectional study to assess the impact of changes in zinc intake on the relationship between vitamin D₃ and insulin resistance risk. Study design and methods: This research was based on data from 9545 participants in the national health and Nutrition Survey (NHANES) from 2005 to 2018. Participants were divided into a low intake group (zinc intake<9.58 mg/ day) and a high intake group (zinc intake: ≥9.58 mg/ day) based on their median daily dietary zinc intake. Results: In this cross-sectional study, serum vitamin D₃ levels were independently associated with the risk of insulin resistance in both the low and high Zinc intakes (β: -0.26, 95%Cl: -0.56~0.04 versus β: -0.56, 95%Cl: -1.01~-0.11). In addition, this association was influenced by different dietary zinc intakes (interaction P < 0.05). Conclusions: Our results suggest that zinc intake may influence the association between serum vitamin D₃ and the risk of insulin resistance. Further randomized controlled trials are needed to provide more evidence of this finding.